PELATIHAN PEMBUATAN PAKAN IKAN DARI FERMENTASI BUNGKIL BIJI KEDELAI (Glycine max .Merri) di DESA TANJUNG SEUMANTOH KABUPATEN ACEH TAMIANG - Tri Mustika Sarjani; Abdul L Mawardi; Fadilah Fadilah (Global Science Society, 2020)
Tanjung Seumantoh villagers are generally farmers, fishermen and entrepreneurs. House yards are used as land to increase family income for entrepreneurship. One of the businesses favored by the community through the home industry is making tempe from soybeans and making palm sugar from palm sugar. Waste from making tempeh and tofu in the form of cake is not used by the community, so it is wasted. The nutritional content of the soybean meal is still potential enough to be used by the community to be used as fish food, so that it can increase the economic income of the community. Based on the above problems, the community service team is interested in utilizing tempe and tofu waste from soybeans to increase community creativity, so increase the economy of citizens. The hope of the dedication team with the training in making fish feed from soybean meal can reduce the problems of partners in fish feed, because the village is also a producer of soybean meal which is organic waste from making tempe and tofu which is the home industry of the community.